Real-time implementation of an enhanced proportional-integral-derivative controller based on sparrow search algorithm for micro-robotics system - Ehab Saif Ghith; Farid Abdel Aziz Tolba (IAES International Journal of Artificial Intelligence (IJ-AI), 2022)
This paper presents a new approach to control the position of the micro-robotics system with a proportional-integral-derivative (PID) controller. By using sparrow search algorithm (SSA), the optimal PID controller indicators were obtained by applying a new objective function namely, integral square time multiplied square error (ISTES). The effeciency of the proposed SSA-based controller was verified by comparisons made with Grey wolf optimization (GWO) algorithm-based controllers in terms of time. Each control technique will be applied to the identified model using MATLAB Simulink and the experimental test facility was conducted using LabVIEW software. The simulation and experimental results show that the performance of SSA-PID controller based on ISTES cost function achieves the best performance among various techniques. Moreover, the SSA technique had the highest performance compared to GWO technique based on rising and setting time and many other performance measurements. Thus, it is recommended to apply SSA for tuning the parameters of PID as it can enhance its performance in micro-robotic systems. It was found that the amount of error is reduced by 50% using SSA than other former experiments.